THE CORRELATION BETWEEN STUDENTS' LEARNING STYLE AND THEIR LISTENING ACHIEVEMENT - Shafira Andriyan (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Learning style is a method in which a student obtains, interprets, and processes information. Understanding the students learning style can help the teacher determine the best teaching method for teaching. By identifying the students learning style, students can assess their strengths and weaknesses. Learning style can also help the students be more concentrated on learning to improve the learning process. The objective of this study was to find out the most preferred learning style and determine whether there is a significant correlation between students learning style and their listening achievement in the 2nd- semester students' English Department UNISMA. In conducting the study, the researcher used the correlational research method. The subjects of this study were 28 students 2nd- semester English Department UNISMA 2020. Furthermore, there were two variables in this research. First was students' learning style (variable X), and second was students' listening Achievement (variable Y). The data were collected through a questionnaire and documentation of students' listening achievements. In analyzing the data, the researcher used descriptive analysis and Pearson Product Moment Correlation in SPSS 20.0. Based on the data analysis, it was found that r analysis was 0.141; it lay on interval 0.00- 0.199, which was interpreted as no correlation. Then, the data showed that auditory learning style was the most preferred, followed by kinesthetic and visual. It is also showed that students' learning style in 2nd- semester student of English department UNISMA was very good with a mean score of 85. Furthermore, there was no correlation between students learning style and their listening achievement.